Pemanfaatan Teknologi Informasi dan Komunikasi Dalam pelaksanaan Kurikulum 2013 di MI Tarbiyatul Athfal - Uswatun Hasanah (STMIK AKBA, 2021)
Information and communication technology (ICT) has advantages over traditional methods in effectiveness and efficiency. Mastering ICT is one of the most important competencies possessed by educators. The purpose of this research is to study how the use of